France : Financial Sector Assessment Program-Technical Note on Stress Testing the Banking Sector. (IMF Staff Country Reports; Country Report ;, 2013)
This technical note discusses key findings of the Stress Testing of the Banking Sector for France. Stress testing analysis was used to capture the most salient risks for banks. The findings support the current focus of Autorite de Controle Prudentiel (ACP) to require banks to build up adequate capital and liquidity buffers. They suggest that the banking system would be able to meet regulatory ratios under most scenarios. Solvency stress tests indicate that banks could cope with deterioration in the economic environment while phasing in capital requirements under Capital Requirements Directive IV.